ANALYSIS OF POTENTIAL ENERGY AND ENVIRONMENTAL IMPACT FROM COAL GASIFICATION THROUGH SIMULATION OF PLASMA GASIFICATION PROCESS OF INDONESIAN LOW-RANK COAL - Priyo Adi Sesotyo; Muhammad Nur; Oki Muraza (Indonesian Mining Journal, 2021)
Indonesia's coal reserve is abundant with its lower price and widely distributed than oil and natural gas. However, the coal emits high carbon dioxide gas (CO2) and sulfur compounds (H2S, SOx) to the environment during utilization. Plasma gasification can overcome those lacks using the external electric energy through a plasma torch. The chemical properties of coal have impacts on the energy content and environmental benchmarking. Using steam as a gasifying agent should be adequate to produce H2 and CO syngas. A research has been carried out to analyze and understand the benefit of using different gasifying agent for maximizing the H2 production and minimizing the environmental impact. Pure Steam (PS) gasifying agent to coal ratio of 0.4 has shown 43.76% H2 composition in syngas and cold gasification efficiency (CGE) with 37.71%. The PS to coal ratio of 0.2 has a significant carbon conversion efficiency of 4.75% and the PS to coal ratio of 0.6 has a gross energy potential of 86.5 kW. Using such the PS is significantly better than the mixture of steam oxygen (SO) as the gasifying agent since it needs to have a greater SO flow rate to have the SO to coal ratio of 1.00.